Knowledge sharing series II by the Securities Industries Development Corporation / Securities Commission Malaysia - Hasli, Anita (Universiti Teknologi MARA, Sarawak, 2016)
BBA (Hons) Finance programme organised the second series of seminars/workshops conducted by the Securities Industries Development Corporation / Securities Commission Malaysia. The Knowledge Sharing series has been scheduled as a series of education seminars and workshops to be held as a long-term annual event for the BBA (Hons) Finance programme. 1 08 students attended the event on the first day held on 1 8 March 2016 at Dewan Kuliah Campus 1. Another group of 1 65 students attended the event on 1 9 March 2016 at the Crowne Plaza Riverside Majestic Hotel, Kuching. The topics covered on the first day were Personal Financial Management and Investors’ Education while the topics on the second day were The Balanced Approach Methodology, Fundamental Analysis and Technical Analysis.